Differential contribution of elbow flexion and knee extension on vascular and hemodynamic parameters and arterial stiffness indices after acute strength exercise in young adults - Patricia Maria Cardoso Santos; Aline Cristina Sierve Oliveira; Leonardo Ribeiro Vieira; Isabel Cristina Gomes; Janaine Cunha Polese; Lucas Túlio de Lacerda; Bruno Almeida Rezende; Danusa Dias Soares; Maria Gloria Rodrigues-Machado (BMC, 2024)
Abstract Background Different types of exercise, performed acutely or chronically, have different repercussions on central hemodynamics, arterial stiffness, and cardiac function. In this study, we aim to compare the effects of acute elbow flexion (EFlex) and knee extension (KExt) exercises on vascular and hemodynamic parameters and arterial stiffness indices in healthy young adults. Methods Young adults (20 to 39 years) underwent randomized muscle strength tests to obtain 1 repetition maximum (1RM) for elbow flexion (EFlex) and knee extension (KExt). After a minimum interval of 48 h, cardiovascular parameters were assessed using Mobil-O-Graph® (Mobil-O-Graph, IEM, Germany) at three-time points: at baseline (before exercise), immediately after elbow flexion or knee extension exercises with a load corresponding to 50% of 1RM (T0) and after 15 min of rest (T15). Results Immediately after exercise (T0), peripheral systolic blood pressure, peripheral pulse pressure, central systolic blood pressure, and central pulse pressure were significantly higher in KExt than EFlex (Δ 3.13; Δ 3.06; Δ 5.65; Δ 5.61 mmHg, respectively). Systolic volume, cardiac output, and cardiac index were significantly higher immediately after KExt when compared with EFlex (Δ 4.2 ml; Δ 0.27 ml/min and 0.14 l/min*1/m2, respectively). The reflection coefficient and the pulse wave velocity were also significantly higher at T0 in KExt compared to EFlex ( Δ 8.59 and Δ 0.12 m/sec, respectively). Conclusion Our results show differential contribution of muscle mass in vascular and hemodynamic parameters evaluated immediately after EFlex and KExt. In addition, our study showed for the first time that the reflection coefficient, an index that evaluates the magnitude of the reflected waves from the periphery, was only affected by KExt.